Sir Fred at the Met The revival of Le Rossignol is seen in New York - Morris, Geraldine (Dance Books Ltd., Alton,Hampshire (UK), 2004)
A revival of Le Rossignol. PALABRAS CLAVE: Le Rossignol, Frederick Ashton, New York, John Dexter.